Cross border cooperation –promoter of tourism development - Agita Slara (European Regional Science Association (ERSA), 2004)
Accord Aydalot (1986), the firm in no heaven-sent agent free to “choose” an environment, it is secrete by its environment. The firm is not an isolated innovative agent but is part of the milieu, which makes it act. The competitive and innovative performance of the territory, territories more or less competitive and innovative, requires persistence and participation of the different actors: companies, institutions of support and assistance to the company's activity, public institutions. We do not have the ambition to cover the whole different actors, but illustrate the approach that reflect the better performance innovative of the companies is associate to different factors of the environment milieu and evaluate the determinant conditions of participation in innovation activities. Our purpose is to analyse the behaviour of the companies of 3 NUTS III of Beira Interior of Portugal, relatively to the innovative initiatives. We use a survey applied to vast set of companies. The methodology is based on the application of the multivariate statistics: k-means analysis clusters that allowed distinguish 3 standard behaviours from the companies. To classify the standard behaviour of the companies and identify the characteristics of each cluster, we applied the crosstabs and compare means. We consider the fowling attributes to the different clusters: process of innovation, the mechanisms of knowledge, the networks and the system of governance. These attributes will help to trace the profile of the innovative behaviours and to perceive which the factors or variables of the environment those are links with the best performance on innovation.
Keywords: 330